Precipitation of the ordered α2 phase in a near-α titanium alloy. (May 2016) - Radecka, A.; Coakley, J.; Vorontsov, V.A.; Martin, T.L.; Bagot, P.A.J.; Moody, M.P.; Rugg, D.; Dye, D.
Abstract: Precipitate evolution in a near- α alloy was studied using transmission electron microscopy (TEM) and correlative atom probe tomography (APT) after ageing at 550–700 for times up to 28 days. It is found that precipitation occurs much faster and is more prolific in samples heat treated at higher temperatures. Particles were spherical after ageing at 550 °C, while after ageing at 700 °C they become ellipsoids with the major axis lying close to the [0001] direction. At longer ageing times, the α 2 precipitates were found to contain greater amounts of Sn + Si, indicating that Sn and Si are stronger Ti3 (Al, Sn, Si) formers than Al.